Leader Behaviour, Emotional Intelligence, and Team Performance at a UK Government Executive Agency During Organizational Change. Issue 2 (2nd April 2016) - Neil, Rich; Wagstaff, Christopher R. D.; Weller, Emily; Lewis, Ryan
ABSTRACT: This paper presents three studies exploring the relationship between performance psychology variables and performance within a UK Government Executive Agency during substantial organizational change. Study 1 examined relationships between transformational leadership behaviours, emotional intelligence (EI), cohesion, and team performance. Task cohesion interacted with EI to predict performance. Specifically, it was found that use of emotions for performance partially mediated the relationship between cohesion and team performance. Study 2 interviewed team leaders about their EI and leadership behaviours and how these influenced cohesion and performance during this organizational change. Team leaders reported using a number of different strategies with their team for cohesion and performance benefits. Study 3 interviewed the head and deputy head of the leaders from studies 1 and 2 about how our findings had been received and were being used. Reported findings from studies 1 and 2 resonated well with the head and deputy, and had been used to develop a leadership charter and skills matrix to monitor leadership behaviours and identify areas for improvement. These studies offer a unique insight into the behaviours of team leaders within the agency, emphasizing the perceived importance of effective leader behaviours and EI for team member cohesion and performance.